10 years of Workshop on Social, Human, and Economics Aspects of Software (WASHES): Results of a Scoping Review - Gomes, Otávio Santos; Batista, Estela Miranda; Braga e Silva, Gláucia; Araújo, Allysson Allex (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2025: Anais do X Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2025.7992, 2025)
The Workshop on Social, Human, and Economic Aspects of Software Engineering (WASHES), established in 2016, serves as an interdisciplinary venue for the Software Engineering research community. As WASHES approaches its tenth anniversary, this study presents a scoping review of its contributions. We systematically analyze publication trends, thematic evolution, influential authors, institutional participation, and geographic distribution across nine editions. Our findings reveal that WASHES has published 100 papers to date, with the social perspective being the most frequently addressed. The workshop has fostered a diverse network of over 300 researchers from 70 institutions across 19 Brazilian states and 4 countries. Our contribution includes a synthesis of WASHES research, analyzing publication distribution by year, citation patterns, and language preferences. We also map the thematic evolution of WASHES and identify emerging research trends over time. Finally, we highlight the most prolific authors and institutions contributing to WASHES.